Occupational Health and Safety Management Systems as a tool for preventing workplace risks in SMEs (Innovation & Development in Engineering and Applied Science, 2023)
Health and safety management in small and medium-sized companies (SMEs) is very deficient because they have fewer resources than large  companies, which affects the low  prevention of occupational risks. The  research objective was to know the  importance and use of health and  safety management standards in SMEs to prevent occupational hazards. For  this, a systematic review of 24 scientific articles in English and Spanish was carried out with a descriptive and exploratory scope. In summary, few studies in SMEs on health and safety management systems, as well as ISO standards, are used, and the evaluation of these management systems is specific for each type of activity. Reasons why developing management standards adapted to the reality of these organizations is essential.
Keywords: Safety at work; Risk management; Accident prevention; Risk assessment; Health and safety culture; Occupational safety